Faktor-faktor Kritis Kesuksesan Proyek Terhadap Kinerja Proyek di PT Wijaya Karya (Persero) Tbk - Sutikno Sutikno (Jurnal Pendidikan Ekonomi Dan Bisnis (JPEB), 2017)
This article aims to determine the effect of the project office management variable, project management system, site conditions, owner involvement, and the capacity of the project management team. The research method used survey. Respondents numbered 250 people. Data analysis using Structural Equation Modeling (SEM). The results show that the variables of the project management office, project management system, site conditions, owner involvement, and project management team capacity have a positive effect on project performance at PT. Wijaya Karya (Persero) Tbk. Keywords: project management office, project management system, site condition, owner involvment, project management team capacity and project performance.